Impact of vitamin D receptor and binding protein gene polymorphisms in clinical and laboratory data of HCV patients: Cross sectional study. Issue 8 (February 2018) - Scalioni, Letícia de Paula; Santos, Betânia Rodrigues dos; Spritzer, Poli Mara; Villela-Nogueira, Cristiane Alves; Laura Lewis-Ximenez, Lia; Pollo-Flores, Priscila; Bordalo Cathalá Esberard, Eliane; Brandão-Mello, Carlos Eduardo; Lampe, Elisabeth; Villar, Livia Melo
Abstract : Abstract: Potential relationship of vitamin D, vitamin D receptor (VDR), and vitamin D binding protein (DBP) have been suggested in the pathophysiology of hepatitis C virus (HCV) infection. The aim of this observational study is to determine vitamin D levels, and VDR and DBP genetic polymorphism according demographic and laboratory data in chronic HCV patients (CHC). A total of 148 CHC patients gave serum samples for testing 25-hydroxyvitamin D (25 (OH)D) level by immunochemiluminometric assay (<20 ng/mL defined as deficient) and donated blood samples to allelic discrimination analysis using TaqMan assays. Analyzed single nucleotide polymorphisms (SNPs) were: VDR- rs7975232 (ApaI) C>A, rs731236 A>G (TaqI), rs1544410 C>T (BsmI), rs10735810 T>C (FokI) and carrier globulin/binding protein (GC)- rs4588 and rs7041 and the haplotype bAt [CCA]. Hepatic fibrosis was assessed using Fib-4 and Forns index. Eighty-two (54.40%) patients demonstrated deficiency of vitamin D and this was associated to AST ( P  = .019 [CI: 1.003–1.034]), total cholesterol ( P  = .038 [CI: 1.004–1.164]), fibrosis grade ( P  < .001 [CI: 0.000–0.844]), and FokI ( P  = .028) allele T presence. Association was found between VDR polymorphism and fibrosis (BsmI andTaqI), triglycerides (TaqI), and HDL (FokI). DBP polymorphism was associated to HCV genotype (GC rs7041), previous HCV treatment, and GGT (GC rs4588). In conclusion, low frequency of vitamin D deficiency was found, but VDR polymorphisms were frequently associated to fibrosis grade suggesting that they could be used as disease evaluation markers to understand the mechanisms underlying the virus–host interaction.